2017
DOI: 10.1016/j.lfs.2017.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Selective sensitiveness of mesenchymal stem cells to shock waves leads to anticancer effect in human cancer cell co-cultures

Abstract: Selective sensitiveness of mesenchymal stem cells to shock waves leads to anticancer effect in human cancer cell cocultures / Foglietta, Federica; Duchi, Serena; Canaparo, Roberto; Varchi, Greta; Lucarelli, Enrico; Dozza, Barbara; Serpe, Loredana. -In: LIFE SCIENCES. -ISSN 0024-3205. -173(2017), pp. 28-35. Original Citation:Selective sensitiveness of mesenchymal stem cells to shock waves leads to anticancer effect in human cancer cell co-cultures You may download, copy and otherwise use the AAM for non-commerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The analyses started looking for the safest conditions for KB cells under SW stimulation in absence of ZnO NCs. Based on the previous literature investigations (Canaparo et al, 2006(Canaparo et al, , 2013Serpe et al, 2011;Foglietta et al, 2017), a fixed number of shots (500 or 1000) was adopted, varying the PPP (29.1, 39.4, 50.3, 61.7, and 74.1 MPa). The cell viability decreased at increasing either the SW energies (from 29.1 MPa up to 74.1 MPa) or the number of shots (either 500 or 1000 shots), as evidenced in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analyses started looking for the safest conditions for KB cells under SW stimulation in absence of ZnO NCs. Based on the previous literature investigations (Canaparo et al, 2006(Canaparo et al, , 2013Serpe et al, 2011;Foglietta et al, 2017), a fixed number of shots (500 or 1000) was adopted, varying the PPP (29.1, 39.4, 50.3, 61.7, and 74.1 MPa). The cell viability decreased at increasing either the SW energies (from 29.1 MPa up to 74.1 MPa) or the number of shots (either 500 or 1000 shots), as evidenced in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…KB cells, seeded into a treated culture flask, in exponential growth phase, where trypsinized and 5 × 10 5 cells per well were plated in culture medium into a 96-well plate (Corning) for the SW treatment as described by others (Canaparo et al, 2008(Canaparo et al, , 2013Foglietta et al, 2017).…”
Section: Single Sw Treatmentmentioning
confidence: 99%
“…SW have also been proposed alone to inhibit the growth of cancer cells. Foglietta et al reported that when mesenchymal stem cells and cancer cells (glioblastoma or osteosarcoma) co-cultures are irradiated with SW, the consequence is a selective cancer cell death related to the ROS production by mesenchymal stem cells [ 163 ]. Otherwise, SW could be employed to permeabilize temporarily cell membrane and improve the uptake of drugs and chemotherapies [ 164 , 165 ], as well for the delivery of nucleic acids [ 166 , 167 ].…”
Section: Mechanical Wave-based Therapiesmentioning
confidence: 99%